2017
DOI: 10.3389/fphys.2016.00679
|View full text |Cite
|
Sign up to set email alerts
|

Differential Bone Loss in Mouse Models of Colon Cancer Cachexia

Abstract: Cachexia is a distinctive feature of colorectal cancer associated with body weight loss and progressive muscle wasting. Several mechanisms responsible for muscle and fat wasting have been identified, however it is not known whether the physiologic and molecular crosstalk between muscle and bone tissue may also contribute to the cachectic phenotype in cancer patients. The purpose of this study was to clarify whether tumor growth associates with bone loss using several experimental models of colorectal cancer ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 62 publications
(76 reference statements)
7
47
0
Order By: Relevance
“…Indeed, examining this organ crosstalk within cachexia may provide important clues to teasing out the mechanisms that drive this morose disease. Our group and others have demonstrated that cancer-induced cachexia does not solely affect skeletal muscle, but that heart, fat, and bone are also impaired (23,26,28,50). In particular, recent observations have implicated that abnormal muscle-bone crosstalk may play a significant role in cancer cachexia.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Indeed, examining this organ crosstalk within cachexia may provide important clues to teasing out the mechanisms that drive this morose disease. Our group and others have demonstrated that cancer-induced cachexia does not solely affect skeletal muscle, but that heart, fat, and bone are also impaired (23,26,28,50). In particular, recent observations have implicated that abnormal muscle-bone crosstalk may play a significant role in cancer cachexia.…”
Section: Discussionmentioning
confidence: 74%
“…In particular, recent observations have implicated that abnormal muscle-bone crosstalk may play a significant role in cancer cachexia. For example, observations generated in several mouse models of CRC, including C26, HT-29, and Apc min/+ , revealed differential bone loss, despite consistent loss of skeletal muscle mass (28). Interestingly, cancellous bone in the femurs of C26 tumor hosts was generally maintained, whereas in the present study, the use of C26 tumor cells to induce LMs was sufficient to drive both skeletal muscle and bone loss (Figure 9), further indicating an exacerbation in bone phenotype with LMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no functional measurements were performed on the bones from ES-2 hosts, our previous evidence suggests that bone content generally correlates with the overall bone strength in cancer cachexia. 67 Although the molecular mechanism(s) responsible for bone depletion in association with the occurrence of OC are not known, high levels of IL-6, as shown in the animals bearing the ES-2 OC, have been previously reported in association not only with the development of paraneoplastic complications, such as cachexia, leucocytosis, and thrombocytosis, but also with the occurrence of hypercalcaemia, a condition responsible for severe loss of bone mass, 68 or juvenile idiopathic arthritis, a systemic inflammatory condition characterized by clinical features that include stunted growth and skeletal abnormalities. 69,70 In this regard, elevated IL-6 seems to play a relevant role by primarily affecting bone turnover, along with increased bone resorption and reduced bone formation.…”
Section: Es-2 Cells Cause Cachexia In Vivomentioning
confidence: 99%
“…69,70 In this regard, elevated IL-6 seems to play a relevant role by primarily affecting bone turnover, along with increased bone resorption and reduced bone formation. 71 Unlike our previous reports describing the occurrence of bone loss following development of colorectal tumours or after prolonged administration of chemotherapy, 48,67 bone tissue is not generally investigated in the experimental models utilized for the study of HGS-OCs. In the clinical setting, OC is not frequently associated with enhanced bone fractures per se or described as a risk factor for the development of osteoporosis, although elevated bone turnover markers were detected in women undergoing risk-reducing salpingooophorectomy to decrease the risk for breast cancer and OC.…”
Section: Es-2 Cells Cause Cachexia In Vivomentioning
confidence: 99%